The Role of Penta Helix Collaboration in Accelerating Bureaucratic Reform and Improving the Quality of Public Services in Papua Province - Risamasu, Ferdinand; Srem, Ade Irma Awayanti; Warokka, Ari (Universitas Mercu Buana, 2025)
Objective: This study examines the role of Penta Helix collaboration in accelerating bureaucratic reform and improving the quality of public services in Papua Province. The Penta Helix model involving government, business, community, academia, and media is expected to create more effective synergies in addressing Papua's bureaucracy and development challenges.Methodology: The research method used is a qualitative approach with data collection through in-depth interviews, observation, and documentation studies at the Papua Provincial Secretariat.Findings: The findings show that despite significant challenges in terms of infrastructure and human resources, cross-sector collaboration can accelerate bureaucratic reform, create more responsive policies, and improve the quality of public services. Good cross-sector coordination and the active role of the community and media are key success factors.Conclusion: This study concludes that the Penta Helix collaboration can be an effective model to accelerate bureaucratic change in Papua by considering local characteristics and strengthening the capacity of related sectors in development.